The international oil market : a case of trilateral oligopoly - Roncaglia, Alessandro; Kregel, J. A. (London : Macmillan, 1984)
This book reviews the world petroleum industry, from its beginning in 1859 up to the early 1980s.The book characterizes the oil market as a "trilateral oligopoly and market developments are seen as outcomes of power struggles among the producing countries, oil companies, and consuming countries.
Translation of: L'Economia del petrolio.
Includes index.
Includes bibliographical references: p. 171-176.
lje 22/01/2019
Loans
Keywords: Petroleum industry and trade